Internationalizing Teacher Education The Northern Illinois University Plan / David G. Gueulette. - Gueulette, David (Distributed by ERIC Clearinghouse, 1987)
In 1986, the College of Education at Northern Illinois University formed a planning committee to examine the role of the college in preparing teachers for increasing global responsibilities and to determine what planning was needed to develop or expand that role. The overall objectives were to internationalize the teacher education curricula and develop an inventory of promising practices promoting international understanding and awareness in teacher education. The seven activities to be internationalized are administrative leadership, curriculum development, faculty development, student awareness, resources, service, and research. Guidelines for each of the activity areas are presented in the form of a principle followed by an interpretation of its potential contribution to international education and a series of questions. Recommendations sent to the College of Education and its Dean after review and consideration of the guidelines by faculty are listed. (MT)